Geopolitical Risk and Military Spending in Poland - Waszkiewicz, Grzegorz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: To examine the impact of geopolitical risk on military spending in Poland in the years 1993–2022. Research Design & Methods: Autoregressive distributed lags, error correction, and Granger causality test were used. Findings: Polish budgetary spending on defence is influenced by geopolitical risk in both the short and long term. Implications / Recommendations: An increase in geopolitical risk motivates the Polish government to increase its military spending. Contribution: The research verifies the theoretical nexus between external security risk and defence burden in Poland, a study which had never been done.